Effective Utilization of Municipal Solid Waste as Substitute for Natural Resources in Cement Industry - Rehman, Abdur; Khan, Kashif Ali; Hamid, Tayyaba; Nasir, Hassan; Ahmad, Izhar; Alam, Muhammad (Salehan Institute of Higher Education, 2020)
The aim of this study was to evaluate the municipal solid waste (MSW) composition of Peshawar city and its affective utilization for energy purpose in the cement industry. A total 14 days consecutive testing of MSW samples was conducted for winter and summer periods for the purpose of evaluation of the waste composition followed by calculating its heating values. Compliance level of MSW at source was determined which was based upon the questionnaire distribution followed by the financial analysis and feasibility evaluation of the project. The results revealed that the average waste composition of the samples consists of organic waste contents (20.72%), combustible items (37.86%), readily saleable items (20.95%) and other miscellaneous waste items (20.46%). Moreover, the samples were then tested for the evaluation of calorific value and it was found that the heating value of MSW is recorded up to 35513 KJ/Kg whereas; the value for coal is around 38000 KJ/Kg. These findings revealed that the replacement of coal by MSW may be more efficient and might be effectively utilized in the production of cement as the energy production of MSW and coal is nearly same. In addition, the utilization of MSW as a replacement of coal has a great potential of enhancing the service life of the landfills. Besides, NPV analysis of this study revealed that the project is worthwhile to be implemented as it shows high returns regarding financial aspects.